Hypermobility among children with autism spectrum disorders and its correlation with anthropometric characteristics - Jaya Shanker Tedla; Faisal Asiri; Mastour Saeed Alshahrani; Kumar Gular (Journal of the Pakistan Medical Association, 2021)
Objective: The objective of the current study was to determine the extent of hypermobility in children with Autism Spectrum Disorder and to determine the correlation between age, gender, height, weight, BMI and hypermobility. Methods: This cross-sectional study included 117 children with Autism Spectrum Disorder aged from 2 to 17 years, of whom 91 were boys and 26 were girls. After obtaining the written informed consent from the parents of these children with Autism Spectrum Disorder, we assessed their level of hypermobility using the Beighton score. Results: Out of 117 children, 47 (40.17%) were normal and 70 (59.83%) showed an abnormal increase in mobility. The average Beighton score was 5.33 ± 2.42 (mean ± SD). There is a moderate negative correlation between height, weight, and age with hypermobility. Conclusion: The extent of hypermobility among children with Autism Spectrum Disorder was 60%, that is, 70 out of 117 children had hypermobility. Our results also suggested that the age, height, weight, and BMI of the child had a moderate negative correlation with hypermobility. Keywords: Autism Spectrum Disorder, Hypermobility, Beighton score, Children and Ligament laxity Continuous...